2003
DOI: 10.1093/ndt/gfg453
|View full text |Cite
|
Sign up to set email alerts
|

A simple risk score predicts poor quality of life and non-survival at 1 year follow-up in dialysis patients

Abstract: A simple risk score based on INTERMED, age (> or =65) and comorbid diabetes (yes/no) can be used to detect patients at risk of poor QoL and non-survival at an early stage of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 21 publications
4
17
0
1
Order By: Relevance
“…A recent single-centre retrospective study showed no significant survival advantage among patients ≥80 years of age choosing RRT over a conservative approach [44]. Several parameters have been identified to be associated with a better survival of elderly patients on dialysis [18, 26, 4549]. In the present study the survival probability was closely linked to the baseline 47-item FACT-An score (see Figure 2).…”
Section: Discussionsupporting
confidence: 47%
“…A recent single-centre retrospective study showed no significant survival advantage among patients ≥80 years of age choosing RRT over a conservative approach [44]. Several parameters have been identified to be associated with a better survival of elderly patients on dialysis [18, 26, 4549]. In the present study the survival probability was closely linked to the baseline 47-item FACT-An score (see Figure 2).…”
Section: Discussionsupporting
confidence: 47%
“…Both nature of the disease and the type of treatment involve side effects such as cardiovascular diseases, metabolic disorders etc. So, it is not far-fetched that role limitations are more seen in this group of patients due to physical problems and pain (34), and the majority of hemodialysis patients has inactive lifestyle (35).…”
Section: Discussionmentioning
confidence: 99%
“…When used by trained health care professionals from different backgrounds, the validity and reliability of the tool has been demonstrated in a variety of medical populations17,18,26,27, including liver transplant recipients 16. The utility of the INTERMED has been demonstrated for detecting complex, medically ill patients at risk for poor HRQOL and decreased response to medical treatment28; it has also proven to be a case-finder for early and beneficial psychosocial interventions 29,30,31Table 1) classifies information into four domains: biological, psychological, social and health care.…”
Section: Methodsmentioning
confidence: 99%